Photoresist Films: Freestanding Photoresist Film: A Versatile Template for Three‐Dimensional Micro‐ and Nanofabrication (Adv. Funct. Mater. 42/2020). (16th October 2020) - Liu, Yuyang; Du, Ke; Wathuthanthri, Ishan; Xu, Wei; Choi, Chang‐Hwan
Abstract : In article number 2004129, Chang‐Hwan Choi and co‐workers introduce a novel sacrificial‐layer‐free lifting‐off process that can release a pre‐patterned photoresist film from a supporting substrate, leveraging the formation of bubbles at the interface during the decomposition of hydrogen peroxide solution. The flexible and durable freestanding film with lithographically defined features can serve as a versatile platform such as template, stencil, and scaffold for rapid, scalable, and robust 3D micro‐ and nanofabrication.